THE BRITISH MUSICIAN’S SELECTED SONGS (A FIGURATIVE LANGUAGE ANALYSIS) (Karya Ilmiah Mahasiswa (KIMA), 2023)
The objective of the study is to classify the figurative language using Leech’s theory in British musician’s selected songs. This study used descriptive qualitative method. The writers take four songs, they are My Guitar Gently Weeps by The Beatles, Slide Away by Oasis, Suck It and See by Arctic Monkeys and Robbers by The 1975. From the results of the study, the writer found 5 types of figurative language, they are 5 hyperbole, 5 metaphor, 2 personification and 2 simile. Further, The writer found that all the 7 types of meaning are contained in British musician’s selected songs, they are 4 conceptual meaning, 6 connotative meaning, 3 collocative meaning, 1 social meaning, 6 affective meaning, 4 reflective meaning and 1 thematic meaning.